Research on the power of non-state-owned shareholders in the board and state-owned enterprises’ innovation investment - Kanghong Li; Xiuying Wang; Yongqi Luo; Zixiao Li (PLoS ONE, 2026)
In the deepening stage of the reform of mixed ownership of state-owned enterprises from “mixed equity” to “reform mechanism”, how to stimulate the vitality of enterprise innovation through effective reform of corporate governance mechanism has become a core issue related to the success or failure of the reform. Existing research mostly focuses on the equity structure of non-state-owned shareholders, but generally ignores the power allocation of the board of directors, which is a key link in transforming equity advantages into governance efficiency. Based on the perspective of board functions, this paper discusses the impact and mechanism of the board of directors’ board power on the innovation investment of state-owned enterprises from 2008 to 2022. The research finds that the power of non-state-owned shareholders in the board has a significant promotion effect on SOEs’ innovation investment. The results of the robustness test show that such a finding holds. According to mechanism analysis, the interplay intensity in the board serves as sort of mediator for the impacts of the power of non-state-owned shareholders in the board on SOEs’ innovation investment. The power of state-owned shareholders in the board plays an inverted U-shaped role in the positive promotion exerted by the power of non-state-owned shareholders in the board on SOEs’ innovation investment, that is, along with the expansion of the power of state-owned shareholders in the board, the positive impacts of the power of non-state-owned shareholders in the board on innovation investment are reinforced before being inhibited.